Strategies for Economic Recovery and Peace In Darfur - Young, Helen; Osman, Abdal Monium; Dale, Rebecca (Tufts Archival Research Center, 2005)
Competing livelihoods in the absence of good local governance has led to localized and ultimately devastating Conflict, Armed (War) over natural resources in Darfur. The lack of comprehensive livelihoods analysis in international peace processes and humanitarian assistance risks entrenching the Darfur Conflict, Armed (War) even further. Livelihoods analysis is a prerequisite for ensuring that resources are allocated according to need between competing livelihood groups i.e. impartiality of humanitarian response, and for appropriate planning/implementation of future recovery and development. To date, the humanitarian response has favoured certain groups while marginalizing others, specifically the Abbala arabs. Based upon intensive field research and consultation, this briefing note explains the background to the livelihoods and economic crisis in the Darfur region, and lays out specific recommendations for how it can be addressed.